Managing human resources - Stone, Raymond J. (John Wiley and Sons, 2013)
Managing human resources, 2nd edition, is an abridged version of Ray Stone's Human resource management, 6th edition, the longest running and most successful Australian textbook ever produced in the field of HRM. Its 16 chapters present a concise coverage of key topics typically taught in a 12 or 13 week teaching semester. Thoroughly updated from the first edition, key features include: integrated coverage of the Workplace Relations Amendment (Work Choices) Act 2005 and its impact on HRM; a thorough exploration of topical issues such as work-life balance, the ageing population and the skills shortage in terms of their effect on organisations, employees and the HR manager; letters to the editor, newsbreaks, case studies, fast facts, research flash boxes, interviews with HR practitioners and a wealth of end-of-chapter activities that provide ample stimulus material for analysis and discussion. Key themes of the text continue to be an emphasis on HRM practice in the Asia-Pacific region, and the importance of strategy and managing diversity in the workplace.